2017
DOI: 10.1111/jocn.13677
|View full text |Cite
|
Sign up to set email alerts
|

Video ethnography during and after caesarean sections: methodological challenges

Abstract: Video ethnographic data are beneficial as it provides exceptionally rich data for in-depth analysis of interactions between the environment, equipment and people in the hospital environment. The analysis of this type of data can then be used to inform improvements for future care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The reviewed studies suggested that video ethnography can support healthcare improvement at a team level. For example, Stevens et al [ 43 ] promoted video ethnography as a way to capture in-depth data on intimate interactions, in their study of elective caesareans. The video data allowed them to make use of timing data (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed studies suggested that video ethnography can support healthcare improvement at a team level. For example, Stevens et al [ 43 ] promoted video ethnography as a way to capture in-depth data on intimate interactions, in their study of elective caesareans. The video data allowed them to make use of timing data (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As far as the operating theatre staff is concerned, authors recommend that theatre staff, including medical students, are asked formally, upon embarking on such a quality initiative, to volunteer to work with the innovation. An official informed consent stating the purpose of the data recordings, where the data recordings are analysed, what the expected benefits for the participants are, and how the data are stored securely may help in gaining support and momentum for the MDR initiative. It should be emphasized that their safety and personal privacy is protected, ensuring full transparency of the methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Video ethnography has been used in the maternity services to capture footage of care during and after caesarean section. This enabled multiple viewing for in-depth analysis [18] but presented challenges such as the "inability of the researcher and camcorder to blend into the environment" and remain unnoticed [19]. Pink and Mackley [20] explained how ethnographic research using the "video tour" method provided insights into "how the sensory aesthetic of home is experienced, produced and maintained" in everyday domestic life.…”
Section: Methodsmentioning
confidence: 99%